Implementation of Physical Education Management based on The 2013 Curriculum - Samiun Alim; Dewi Maya Sari; Rinaldi Aditya; Susilawati, Susilawati (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2022)
This study aims to determine the extent of the implementation of learning management of physical education teachers based on the 2013 curriculum in junior high schools in Medan City. This research uses descriptive research type, the location of this research is carried out in several junior high schools in Medan City. From the data on the results of physical education management based on the 2013 curriculum which consists of planning, implementation and evaluation in this study relevant to the framework that has been developed based on theories that support research in this study obtained the following data: 1) Physical education planning management based on the 2013 Curriculum at State Junior High School in Medan City obtained a value of 660/750 x 100% = 88% or with a category classified as very strong; 2) physical education implementation management based on the 2013 Curriculum at State Junior High School in Medan City obtained a value of 706/800 x 100% = 83.3% or with a category classified as very strong; 3) physical education evaluation management based on the 2013 Curriculum at State Junior High School in Medan City obtained a value of 706/800 x 100% = 83.3% or with a category classified as very strong.